Pengaruh Pemahaman Perangkat Desa Dan Peran Perangkat Desa Terhadap Akuntabilitas Pengelolaan Dana Desa (Studi Kasus Pada Desa di Kecamatan Sangkapura Kabupaten Gresik) - Masriyah Masriyah; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The purpose of this research is to analyze and discuss the effect of understanding village officials and the role of village officials on the accountability of village fund management. This research is a quantitative research with technical data collection using a questionnaire. The sample in this study amounted to 97 respondents. The location of this research was village officials in Pudakittimur Village, Pudakit Barat Village, and Suwari Village, Sangkapura sub-district, Gresik Regency. The sampling technique used is purposive sampling method. Processing of primary data using analysis of Statistical Package for Social Science (SPSS) version 25. technique with multiple regression analysis method. The results of this study indicate that simultaneously the independent variables have a significant effect on the dependent variable, while partially each variable has a positive and significant effect on the accountability of managing village funds.Keywords : Understanding of village officials, the role of village officials, and accountability for managing village funds